Forward to the Past. The Teaching of History and State Ideology Changes in Russia at the Beginning of the XXI Century - Wojciech Siegień (University of Lower Silesia, 2016)
The article analyses changes of Russian official state ideology on the example of education, namely the planned changes in the history teaching syllabus. Elements of Russian educational macro-politics were analysed on the basis of the media monitoring of 2014-2016 period. Russia under Putin, as an authoritarian state, seeks for ideological unification, which in the context of history teaching means that the "historical and cultural standard" needs to be worked out. It results in adaptation of the official version of tradition to current ideological needs of the state. In addition, the role of the teacher has been reduced to transmitting the "monologue of meanings" in order to communicate students the public "objective" knowledge.